Recent Mechatronics Advancements in Cement & Power Industries for Coal Unloading - Kumar Sen, Sourabh; Sen, Garima; Singh Rajpurohit, Vikram (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we are presenting Mechatronic techniques which are used in industries for loading and unloading of raw materials. This paper introduces the process of the wagon loading and unloading of the raw materials presently used in the cement and other manufacturing industries. Mainly the Wagon system are used in mines, power plants, cement plants and other industries for loading the raw material and transporting them to other process of manufacturing. And the wagon unloading system is used for unloading the raw material received from the mines by the railway wagons. In industries BOXN and BOBRN wagons are frequently used. For loading and unloading the Wagons, coal conveying system is used that contains so many mechanical equipment. Presently there are mainly two types of wagon loading systems (a) Stationary Rake and moving loader (b) Moving rake and stationary loader In this paper, we are presenting latest technologies of recent tipplers that are automation based. Their controlling is done through many sensing instruments which is very effective and extensive. They are fail safe, accidental safe and environment friendly too. PLC SCADA is being used for proper automation controlling which may call mechatronics as whole.